2011
DOI: 10.1103/physrevb.84.195468
|View full text |Cite
|
Sign up to set email alerts
|

Single-color pyrometry of individual incandescent multiwalled carbon nanotubes

Abstract: Objects that are small compared to their thermal photon wavelengths violate the assumptions underlying optical pyrometry and can show unusual coherence effects. To investigate this regime we measure the absolute light intensity from individual, incandescent multiwalled carbon nanotubes. The nanotube filaments' physical dimensions and composition are determined using transmission electron microscopy and their emissivities are calculated in terms of bulk conductivities. A singlecolor pyrometric analysis then ret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…Carbon fibers are expected to withstand a certain critical temperature depending upon the conditions of the atmosphere. In other carbon allotropes, such as multiwalled CNTs, this temperature has been estimated to be around 2400 K [58], and 3200 K [20,59] in high vacuum conditions. In the case of the lower bound, the value also corresponds to the sublimation temperature of graphite in vacuum conditions [60].…”
Section: Simulation Of Joule Heating Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Carbon fibers are expected to withstand a certain critical temperature depending upon the conditions of the atmosphere. In other carbon allotropes, such as multiwalled CNTs, this temperature has been estimated to be around 2400 K [58], and 3200 K [20,59] in high vacuum conditions. In the case of the lower bound, the value also corresponds to the sublimation temperature of graphite in vacuum conditions [60].…”
Section: Simulation Of Joule Heating Temperaturementioning
confidence: 99%
“…where is the thermal conductivity, the temperature, the applied current, the applied voltage and the length. It can be shown that the solution to Equation (1) is given by [58]:…”
Section: Simulation Of Joule Heating Temperaturementioning
confidence: 99%
“…3G as a function of the heater power. As expected for a small device in vacuum that is too cool to radiate appreciably, the temperature is linear in the applied power (6). When working either with devices or with lamellae deployed as local thermometers, a plot such as Fig.…”
mentioning
confidence: 98%
“…However, previous carbon materials, both bulk and nano, ultimately failed to compete with tungsten filaments for efficient lighting. Although numerous carbon nanotube and graphene‐based incandescent sources have been demonstrated, only a few reported operating temperatures T exceeding 2000 K, and none could achieve the T > 3000 K required to compete with tungsten filament light bulbs. The Stefan–Boltzmann law dictates that the radiation output scales as T 4 , and higher T results in comparatively more radiation in the visible range than the infrared so a high operating T enhances both power density and efficiency.…”
mentioning
confidence: 99%